The Development of an Information Society and Electronic Commerce in the European Union in the Context of Selected Documents of the EU and International Organisations - Hibner, Jacek (Comparative Economic Research. Central and Eastern Europe, 2012)
Due to the rapidly growing use of the Internet, the development of electronic commerce (defined by the World Trade Organization as “the production, distribution, marketing, sale or delivery of goods and services by electronic means”1) has become one of the key aspects of today’s sustained growth. It influences productivity, facilitates the international movement of goods and services, and stimulates export and import trade. The European Union, as well as many multinational organisations, is working towards the harmonisation of their rules, and to facilitate and streamline this kind of international exchange. In this article, the author presents selected documents on electronic commerce published by the United Nations Commission on International Trade Law, the World Trade Organization, the Organisation for Economic Cooperation and Development, the International Chamber of Commerce and the European Union since 1994.